Peran Puspaga Semanggi Dalam Pelayanan Masyarakat di Kota Surabaya - Muchammad Romli; Tri Kartika Pertiwi (Universitas Negeri Surabaya, 2025)
This activity aims to analyze the role of Puspaga Semanggi in improving the quality of community services in Surabaya city, especially in the field of family development and child protection. The method used is a descriptive approach through interviews and direct observation during the internship program at the Office of Women's Empowerment and Child Protection and Population Control and Family Planning (DP3APPKB). This activity found that Puspaga Semanggi has a significant contribution in providing counseling, education, socialization, and guidance services supported by the One Stop Service strategy. Programs such as Pre-Marriage Classes, parenting, and webinars show effectiveness in reaching the wider community. In conclusion, Puspaga Semanggi plays an important role as a preventive measure in improving social welfare, with the support of professional workforce and community involvement.